2016
DOI: 10.1016/j.socscimed.2016.01.026
|View full text |Cite
|
Sign up to set email alerts
|

Proportionate universalism in practice? A quasi-experimental study (GoWell) of a UK neighbourhood renewal programme's impact on health inequalities

Abstract: Recommendations to reduce health inequalities frequently emphasise improvements to socio-environmental determinants of health. Proponents of 'proportionate universalism' argue that such improvements should be allocated proportionally to population need. We tested whether city-wide investment in urban renewal in Glasgow (UK) was allocated to 'need' and whether this reduced health inequalities. We identified a longitudinal cohort (n = 1006) through data linkage across surveys conducted in 2006 and 2011 in 14 dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
53
1
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(59 citation statements)
references
References 37 publications
1
53
1
4
Order By: Relevance
“…On the other hand, the longitudinal sample (although over 1,000 cases) is a little small for the number of variables included in the analysis, and hence some variables had similar effects in the two samples but were not statistically significant in the Markov models. Previous sensitivity analyses have also confirmed that the longitudinal sample and the repeat cross‐sectional samples in our study yield similar findings with regard to health outcomes (Egan et al., ).…”
Section: Discussionsupporting
confidence: 88%
“…On the other hand, the longitudinal sample (although over 1,000 cases) is a little small for the number of variables included in the analysis, and hence some variables had similar effects in the two samples but were not statistically significant in the Markov models. Previous sensitivity analyses have also confirmed that the longitudinal sample and the repeat cross‐sectional samples in our study yield similar findings with regard to health outcomes (Egan et al., ).…”
Section: Discussionsupporting
confidence: 88%
“…However, the association between anxiety over lack of privacy and the specific type of worker housing, such as company dormitories, has yet to be clarified. Company dormitories have never been studied as a factor related to health, although past studies examining the relationship between housing type and mental health have investigated the ownership status of the house ( tenure housing or not) [12][13][14] , the building type (high-rise or low-rise accommodations) 15,16) , the form of housing (detached house or apartment) 17,18) , the size of the residence (small, medium, or large) 19) , or property ownership (public housing or private housing) 20) as factors affecting mental health. Therefore, it is essential to add new information regarding the association between different housing types, such as company dormitories, and anxiety over lack of privacy.…”
Section: Introductionmentioning
confidence: 99%
“…The concept of dose is further complicated where an intervention acts at different socioecological levels that have multiple different mechanisms of action 33 34. The evaluation of GoWell housing regeneration in Glasgow found that reductions in health inequalities were confined to ‘higher investment areas’ 35. Mental health improvements achieved through the Dutch District Approach were limited to districts that implemented more intensive programmes 29.…”
Section: Discussionmentioning
confidence: 99%